Pemetaan Kondisi Sifat Fisik Tanah di Subak Jatiluwih Kecamatan Penebel, Kabupaten Tabanan - RIZKY DELLI ZULKARNAEN; I NYOMAN SUNARTA; NI MADE TRIGUNASIH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Mapping the condition of physical properties of land in Jatiluwih Subak, Penebel District, Tabanan Regency Jatiluwih Subak has different slopes and slopes which are quite calculated for sustainability in the environment by knowing the physical properties of the soil and the management of rice fields on slope farms. To find out the conditions and land management on the slopes it is necessary to investigate the physical properties of the soil, together with the management of land in reality. Research conducted by survey methods and soil samples taken were analyzed at the Soil and Environmental Laboratory, Faculty of Agriculture, Udayana. Whereas land management data was obtained through interviews with soil samples. The purpose of this study was to determine the physical properties of the soil and the reality treatment of different slope gradients in Subak Jatiluwih, Penebel, Tabanan Regency. Research begins with making maps using the Geospatial Information System application by overlaying the soil type map, slope slope map, and land use map. Four homogeneous land were obtained and each soil unit was taken as a composite sample and analyzed the physical properties of soil in the laboratory which included texture, specific gravity, porosity, permeability, and infiltration. The condition of the physical properties of land in Jatiluwih Subak varies. Bulk Density has criteria of low to moderate, porosity conditions between good to shaft, soil permeability has the criteria of being moderate, rather quickly advancing water or air in the soil. Soil infiltration conditions tend to be the same ie fine pores. Research on the location of soil texture shows the presence of clay, clay loam, and loam.